EMPOWERMENT OF BUSINESS SERVICE COOPERATIVES PASIR BATANG SEJAHTERA IN CREATIVE ECONOMIC DEVELOPMENT OF THE COFFEE SECTOR, KARANGSARI VILLAGE, KUNINGAN REGENCY - Mariane, Ine; Palls, Aswin; Ariesmansyah, Andre (Pasundan International of Community Services Journal (PICS-J), 2024)
Cooperatives are an important part of the nation's economic system which is believed to be a financial institution that favors the weak economic group, and is one of the spearheads of the people's economy in accordance with Article 3 of the Cooperative Law Number 25 of 1992. Kuningan has 570 cooperatives, but only 440 cooperatives have a healthy status. The remaining 170 cooperatives are in a vacuum. The Pasir Batang Sejahtera Multipurpose Services Cooperative is one of the cooperatives engaged in all-round business services which includes the following business units. Coffee cultivation and processing services, Tourism Management Services, Agro Business Processing Services (agriculture, animal husbandry) and Community Empowerment Services consisting of the people of Karangsari Village, Darma District, Kuningan Regency and surrounding areas. Cooperatives are one of the sectors that have most felt the impact of the Corona Virus (Covid-19) outbreak, including the Pasir Batang Sejahtera Multipurpose Services Cooperative experiencing problems. Limited human resources, especially understanding of the management of cooperatives in the tourism sector, do not yet have a business network or partnership (Policy). Network) to develop existing business potential and problems that have not been able to respond to changes, especially changes in the market environment during the COVID-19 pandemic, which must follow health protocols. The approach method used in the Community Empowerment Program is as follows: 1. Training, which includes MSME management and networking, as well as analysis of market destinations and digital marketing in supporting tourism promotion 2. Mentoring,